Measuring Accessibility of Green Spaces for the Health and Wellbeing of Inhabitants of the Milan Metropolitan Area - Maria Chiara Pastore; Claudia Ida Maria Parenti; Corinna Patetta (Land)
Several studies have recognised the importance of urban green spaces (UGSs) in modern cities. However, the distribution and accessibility of green spaces represent a challenge for the sustainable development of territories in terms of fair distribution, reducing inequalities, and mitigating the effects of climate change, such as urban heat islands and runoff. This research identifies every UGS capable of contributing to people’s physical and mental wellbeing in the Milan metropolitan area (MMA), one of the most densely populated areas in Europe. The method allows for the various UGSs to be identified and classified using a comparative approach that considers both formal and informal green spaces through a qualitative territorial analysis and the support of open access databases (satellite and thematic maps). Based on this classification, this contribution establishes an ‘accessibility map’ of the metropolitan area that determines the actual pedestrian accessibility of a UGS within 300 m. The results show that only 37% of the residential surface of the metropolitan area offers access to a UGS within a five-minute walk. This research aims to identify the most fragile segment of the MMA, which is pivotal for the tree-planting activities sponsored by the Forestami project.